Pendidikan Multikultural Berbasis Pancasila (Konsep, Nilai dan Falsafah dalam Bingkai Ke-Indonesia-an) - Nur Ali Yasin; Arini Hidayati; Wiwik Nurlailin (Sumule Indonesia Publishing, 2025)
Indonesia, the world’s largest multicultural country, exhibits high cultural, ethnic, religious, and social diversity. This diversity is a gift as well as a major challenge that must be managed wisely so as not to trigger social conflict. This article discusses the importance of multicultural education as a strategic solution to strengthen peace, justice, unity, democracy, tolerance, and religiosity amidst the nation's diversity. Through a qualitative descriptive approach based on literature studies, data are analyzed using content analysis to identify, understand, and examine the main themes surrounding multicultural education, tolerance, democracy, appreciation for diversity, and reconstruction of national culture. The results of the study show that multicultural education can foster an attitude of mutual respect, respect for differences, and develop an inclusive national identity. The implementation of Pancasila Education with a multicultural perspective is a fundamental effort in building awareness of diversity as a national strength. Multicultural education needs to be instilled from an early age through the national education system to build a peaceful, just, and civilized society amidst the plurality of Indonesian culture.